Intermittent EGFR-TKI therapy is associated with durable response in advanced EGFR-mutant NSCLC: a case report - Tan, Sin Nee; Ibrahim, Aishah; Abdul Razak, Megat Razeem; Abdul Azih, Muhammad Naimmuddin; How, Soon Hin (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2023)
Madam S, who diagnosed to have stage IV lung adenocarcinoma with exon 21 L858R point mutation (T3N2M1a) was admitted for massive pericardial effusion in April 2016. She was ECOG 4 on admission. Her ECOG improved to 1 after pericardial tapping and initiation of free sample erlotinib 100 mg daily. Repeated CT thorax post treatment showed the disease was partial responded. Due to financial constraints, she had never bought any EGFR-TKI. She was given a free sample of erlotinib intermittently for total of 12 months followed by intermittent afatinib supply for 2 years. Due to this limited supply, she took half doses of afatinib by cutting a 40 mg tablet once every few days to sustain the continuation of cancer treatment. No major side effects were observed and she remained ECOG 0 with good weight gain. Up to her last clinic visit in September 2021, her PFS was more than 5 years. Intermittent doses of EGFR-TKI may prolong PFS in patients with advanced EGFRm+ NSCLC who has limited treatment options.